Efektivitas Konseling Individual dengan Pendekatan Psikoanalisis Klasik dalam Meningkatkan Resilensi Akademik Siswa Bertipe Kepribadian Sensing dan Feeling - Karnangsyah, Emi; Prasetia, Agung Tri (Jurnal Aplikasi IPTEK Indonesia, 2020)
This study aims to examine the effectiveness of individual counseling services using a classical psychoanalytic approach in enhancing academic resilience among students with Sensing and Feeling personality types. The study participants consisted of 65 tenth-grade students at SMAN 2 Kota Sungai Penuh, grouped based on the MBTI test results. Resilience measurements were conducted through pretest-posttest assessments, before and after the intervention. The results indicated a significant increase in academic resilience in both personality groups, with a greater increase observed in students with the Feeling type. A paired sample t-test revealed significant differences in academic resilience before and after counseling in both personality types, while an independent sample t-test confirmed differences in the intervention’s impact across the types. These findings suggest that the classical psychoanalytic approach effectively helps students understand emotional conflicts and boosts academic resilience, particularly among Feeling-type students. This study recommends tailored counseling approaches based on personality types for optimal results